Utilization of Mobile Phones for Agricultural Purposes by Farmers in Itu Area, Nigeria - Asa, U. A.; Uwem, C. A. (European Scientific Journal, ESJ, 2017)
The study ascertained the agricultural purposes mobile phones are used for by farmers in Itu Local Government Area of Akwa Ibom State, Nigeria. Data were obtained from 150 farmers using a multi-stage sampling procedure, and analysed using descriptive statistics. Findings reveal that the mean age of the farmers was 49 years; their average monthly income was N30,133.83; 59.5% of them were females; 97.3% of the respondents were functionally literate; the average years of farming experience of the respondents was 12 years; and their average household size comprised six persons. Majority of the respondents (98.7%) had access to mobile phones in the study area and majority of them (90.5%) actually owned mobile phones. Getting information from fellow farmers, marketing of produce, accessing inputs for farming, getting agricultural information from radio and the internet, and accessing extension services were the major agricultural uses of mobile phones by farmers in the study area. It is recommended that agricultural extension agencies in Akwa Ibom State focus their attention on these identified agricultural uses of mobile phones to ensure increasing the effectiveness oftheir extension efforts.